2015
DOI: 10.1128/jvi.01798-15
|View full text |Cite
|
Sign up to set email alerts
|

Cocirculation of Two env Molecular Variants, of Possible Recombinant Origin, in Gorilla and Chimpanzee Simian Foamy Virus Strains from Central Africa

Abstract: Simian foamy virus (SFV) is a ubiquitous retrovirus in nonhuman primates (NHPs) that can be transmitted to humans, mostly through severe bites. In the past few years, our laboratory has identified more than 50 hunters from central Africa infected with zoonotic SFVs. Analysis of the complete sequences of five SFVs obtained from these individuals revealed that env was the most variable gene. Furthermore, recombinant SFV strains, some of which involve sequences in the env gene, were recently identified. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 72 publications
(96 reference statements)
9
49
0
Order By: Relevance
“…8A and B). Two gorilla SFV genotypes that differ mostly in the central region of the env gene infect humans and NHPs (20), and we recently described coinfection by strains from the two genotypes (15). Binding magnitude to peptide N 96 -V 110 did not differ between individuals found to be infected with one or two SFV genotypes (Fig.…”
Section: Figmentioning
confidence: 85%
See 1 more Smart Citation
“…8A and B). Two gorilla SFV genotypes that differ mostly in the central region of the env gene infect humans and NHPs (20), and we recently described coinfection by strains from the two genotypes (15). Binding magnitude to peptide N 96 -V 110 did not differ between individuals found to be infected with one or two SFV genotypes (Fig.…”
Section: Figmentioning
confidence: 85%
“…A single SFV-infected individual exclusively recognized peptide N 96 -V 110 -cae_agm22, whereas 31 recognized peptide N 96 -V 110 . All SFV sequences from Central African hunters and NHPs had a W at position 108 (9,20), including the two individuals whose plasma samples reacted with peptide cae_agm22. We cannot exclude the presence of gorilla SFV quasispecies carrying a W108R change in body compartments other than blood or their circulation prior to sampling.…”
Section: Discussionmentioning
confidence: 99%
“…The large number of studies demonstrating broad distribution of SFVs in Old World and New World NHPs and species-specific prevalence of SFV strains have been based on sequence analysis of genomic regions [8,[24][25][26][27][28][29][30][31][32][33][34]. Whole-genome analysis of some isolates has shown that genetically-diverse SFV strains circulating in different NHP species have contributed to the generation of recombinant viruses involving the SU region in env [11,12,35]. It is noted that sequence variation in SU was initially characterized in feline foamy viruses [36].…”
Section: Discussionmentioning
confidence: 99%
“…These variants differed greatly (>30% variability at the nucleotide level) in a 753-bp-long region located in the receptor-binding domain of SU, whereas the remainder of the env gene was largely conserved. Analysis of recombination, by different methods, suggests that the variants emerged through recombination events between different strains, although not all parental strains could yet be identified [13]. Preliminary data provided evidence for dual infection with strains from different genotypes in gorillas, chimpanzees and humans.…”
Section: Summary Of Scientific Sessionsmentioning
confidence: 99%